Blood monitoring in the English Premier League: Effect of curcumin supplementation on blood biomarkers of recovery - Daniels, D.; Lewis, N. A.; Newell, J.; Bruinvels, G.; Roshan, D.; Catterson, P.; Harley, J.; Newell, M.; Barr, A.; Pedlar, C. R. (The Journal of Sport and Exercise Science, 2023)
Reducing inflammation during periods of frequent match play may be an important objective to promote player recovery and protect player health. The authors aimed to investigate the effect of curcumin supplementation on biomarkers of recovery in response to weekly match play during an English Premier League (EPL) season. We conducted a longitudinal analysis of 18 EPL games during the 2019 - 2020 season (n = 22), and used an interrupted time-series design to analyse the effect of curcumin supplementation on biomarkers of inflammation and pro-oxidant status. Participants consumed 2 × 500 mg capsules (Elite Opti-Turmeric, Healthspan, Ltd) for a total dose of 1000 mg of curcumin (as recommended by the manufacturer), the morning of game day -2 (GD-2), game day -1 (GD-1) and immediately post-game during each supplementation period. Relationships between biomarkers and co-variates were examined using linear mixed effects models. No significant effect was found for the intervention on C-reactive protein (CRP) responses. No significant relationships were observed for all other explanatory variables on CRP responses. We found a significant association between hydroperoxides (HPX) responses and time (0.005 mmol/L H2O2; p = 0.020). No significant effect was found for the intervention on HPX responses. No significant relationships were observed for all other explanatory variables and HPX. We report that curcumin ingestion at the dose and protocol prescribed is not effective, at least at a group level, for attenuating biomarker responses within the applied setting of professional soccer.